Manajemen Diet Rendah Kalium pada Pasien dengan Diangnosa Medis Chronic Kidney Disease (CKD) E. C Hiieperkalemia di Ruangan Matahari RSUD dr. TC. HILERS Maumere - Maria Ertina Seja; Yustina Yantiana Guru (Pusat riset dan Inovasi Nasional, 2024)
Chronic Kidney Disease (CKD) with et causa Hyperkalemia is one of the highest causes of death in Indonesia as well as in Sikka district. Based on data obtained in 2022, there were 300 cases of the largest CKD in 25 sub-districts, based on data in the Matahari room there were 22 cases recorded. The aim of this research is to enable prospective nurses to apply professional practices and manage a low potassium diet in hyperkalemia patients to reduce potassium levels in the Matahari Room at RSUD dr. T.C. HILERS Maumere. This research is a case study research using the case study method which begins with identifying previous nursing care reports or via the internet The results of the study showed that there was a decrease in potassium levels in the participants as evidenced by the results of potassium examinations from 6.5 mmol/L down to 5.0 mmol/L. From the research results it can be concluded that low potassium diet management is very influential in helping to reduce potassium levels in the blood. Suggestions for relevant agencies are that low-chlorium diet management can be used as a nursing care option for patients with Chronic Kidney Disease. It is hoped that by knowing the effect of a low potassium diet on hyperkalemia sufferers, it is hoped that this can be an input for improving the quality of services in further nursing care.